#TITLE_ALTERNATIVE# - MAULANA NUGRAHA (NIM : 10312019), FADLI
Ultraluminous X-ray sources (ULXs) are defined as non-nuclear point-source objects with apparent X-ray luminosity higher than that of stellar-mass black hole, typically LX> 2ÃƒÂ—1039 erg s-1, in the 0.3-8 keV band. Until now, there is still no clear consensus what physical processes take place and by what kind of objects are ULXs powered. ULXs are often explained using two different scenarios, either (1) ULXs as intermediate mass black hole (IMBH) with sub-Eddington accretion or (2) ULXs as stellar mass black hole with super-Eddington accretion. There are two methods that commonly used to study ULXs. We can study the X-ray spectra of ULXs, or we study how population of ULXs correlate with their environment, in this case the host galaxies. The main goals of this Thesis is to study: (1) effects of inclination correction of the host galaxies to ULXsÃ‚Â’ distribution, and (2) relations of metallicity with other properties of the ULXs host galaxies. The data we use are based on two catalogues of ULX candidates, i.e. from Liu (2011) and Walton et al. (2011), that have been combined and selected by Priajana (2016). After re-exemination and re-selection of the ULX candidates and their host galaxies we obtained 559 ULXs in 233 host galaxies. Further analysis was focused on ULXs with inclination-corrected distance r ≤ R25 from the center. We checked correlations of ULXs in the sample with the properties of their host galaxies, such as distribution of ULXs with distance from the center of the host galaxies (inclination corrected), correlation of metallicity with other properties of the host galaxy (Hubble type, luminosity, stellar mass, and SFR), and distribution of ULXs with metallicity of the host galaxies. From this study we found that inclination correction shifts many ULXs to be outside R25 of the host galaxies, making them as suspected contaminants, and that relations of metallicity with other properties of the host galaxies (Hubble type, luminosity, and stellar mass) follow general trends commonly obeyed by galaxies.